Ecological cognition: expert decision-making behaviour in sport - Araújo, D.; Hristovski, R.; Seifert, L.; Carvalho, J.; Davids, K. (International Review of Sport and Exercise Psychology, 2019)
Expert decision-making can be directly assessed, if sport action is understood as an expression of embedded and embodied cognition. Here, we discuss evidence for this claim, starting with a critical review of research literature on the perceptual-cognitive basis for expertise. In reviewing how performance and underlying processes are conceived and captured in extant sport psychology, we evaluate arguments in favour of a key role for actions in decision-making, situated in a performance environment. Key assumptions of an ecological dynamics perspective are also presented, highlighting how behaviours emerge from the continuous interactions in the performer-environment system. Perception is of affordances; and action, as an expression of cognition, is the realisation of an affordance and emerges under constraints. We also discuss the role of knowledge and consciousness in decision-making behaviour. Finally, we elaborate on the specificities of investigating and understanding decision-making in sport. Specifically, decision-making concerns the choice of action modes when perceiving an affordance during a course of action, as well as the selection of a particular affordance, amongst many that exist in a landscape in a sport performance environment. We conclude by pointing to some applications for the practice of sport psychology and coaching and identifying avenues for future research.